Biomimetics: Tunable Anisotropic Wettability of Rice Leaf‐Like Wavy Surfaces (Adv. Funct. Mater. 5/2013). (1st February 2013) - Lee, Seung Goo; Lim, Ho Sun; Lee, Dong Yun; Kwak, Donghoon; Cho, Kilwon
Abstract : Inspired by the hierarchical structures of rice leaf surfaces, synthetic rice leaf‐like wavy surfaces with tunable anisotropic wettability are described by Kilwon Cho and co‐workers on page 547 . The nanometer scale roughness of the rice leaf‐like surfaces is controlled to yield tunable anisotropic wettability and hydrophobic properties that transition between the anisotropic/pinned, anisotropic/rollable, and isotropic/rollable water droplet behavior states.